Hypoglycaemia and monitoring practices following insulin-dextrose therapy for hyperkalaemia - Samuel Ford; Julian Williams; Ian Coombes; Adam La Caze (JEM Reports)
Background: Hypoglycaemia is commonly encountered following insulin-dextrose therapy (IDT) for hyperkalaemia. This retrospective study aimed to assess the local incidence of hypoglycaemia following IDT for hyperkalaemia in the Emergency Department (ED). Objectives: Describe the local incidence of hypoglycaemia and BGL monitoring practices following IDT for hyperkalaemia in the ED. Methods: Adult patients with hyperkalaemia (>5.5 mmol/L) who received IDT in a large metropolitan ED were included. The primary outcome was the incidence of hypoglycaemia, defined as a BGL less than 70 mg/dL (3.9 mmol/L), within 5 h post-administration. Secondary outcomes included hypoglycaemia severity, time to hypoglycaemia, risk factors for hypoglycaemia, blood glucose and potassium monitoring. Data collection spanned January 1, 2019 to May 1, 2020. Results: Among 90 patients, 51 % were receiving chronic renal replacement therapies and the incidence of hypoglycaemia and severe hypoglycaemia was 30 % and 6.7 % respectively. Risk factors for hypoglycaemia were lower pre-treatment blood glucose (p=<0.001), absence of diabetes (p=<0.001) and not being prescribed insulin prior to presentation (p = 0.0026). Approximately 50 % of patients received ≤2 blood glucose measurements within 5 h post IDT. Only 44 % of patients had a potassium sample taken in the 1st hour post IDT and 24 % in hour 3. Conclusions: This study demonstrates a higher incidence of hypoglycaemia post-IDT for hyperkalaemia than reported in the general population and estimates the incidence of severe hypoglycaemia in an Australian population. Monitoring of both blood glucose levels (BGL) and potassium was suboptimal. Strategies to improve BGL monitoring and prospective studies to define the optimal dose of insulin-glucose for hyperkalaemia are needed.